2012
DOI: 10.1292/jvms.12-0050
|View full text |Cite
|
Sign up to set email alerts
|

Porcine Granulocyte-Macrophage Colony-Stimulating Factor Improves the <i>in vitro</i> Development of Cloned Porcine Embryos

Abstract: ABSTRACT. We examined the effects of porcine granulocyte-macrophage colony-stimulating factor (pGM-CSF) on the in vitro development of porcine embryos produced by somatic cell nuclear transfer (SCNT) for the first time. We evaluated the effects of pGM-CSF on SCNTderived blastocyst formation and investigated gene expression. A total of 522 cloned embryos in 6 replicates were treated with 10 ng/ml pGM-CSF during in vitro culture (IVC). This treatment significantly (P<0.05) increased blastocyst formation and tota… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 47 publications
1
9
0
Order By: Relevance
“…To further explore the effect of combined treatment-mediated the reduced 5mC and H3K9me2 on SCNT embryo development, we examined protein expression of two key transcription factors including OCT4 and CDX2 at the blastocyst stage after combined treatment or TSA treatment alone. The reduced expression of OCT4 and CDX2 in porcine somatic cloned blastocysts compared with IVF counterparts has been reported in the previous studies [26,35]. Analogous to this, we observed that expression levels of OCT4 and CDX2 in SCNT blastocysts were lower than that in in vivo and in vitro fertilized counterparts.…”
Section: Discussionsupporting
confidence: 89%
“…To further explore the effect of combined treatment-mediated the reduced 5mC and H3K9me2 on SCNT embryo development, we examined protein expression of two key transcription factors including OCT4 and CDX2 at the blastocyst stage after combined treatment or TSA treatment alone. The reduced expression of OCT4 and CDX2 in porcine somatic cloned blastocysts compared with IVF counterparts has been reported in the previous studies [26,35]. Analogous to this, we observed that expression levels of OCT4 and CDX2 in SCNT blastocysts were lower than that in in vivo and in vitro fertilized counterparts.…”
Section: Discussionsupporting
confidence: 89%
“…In the mouse, blastocysts cultured with CSF2 in the medium experienced reduced expression of specific genes involved in stress responses and apoptosis (Chin et al, 2009) and fewer apoptotic cells after freeze/thawing (Desai et al 2007). In the pig, CSF2 affected gene expression in the blastocyst (Kwak et al 2012a) and increased the ratio of trophectoderm to inner cell mass (Kwak et al, 2012b). Embryos cultured with CSF2 have increased competence to develop to term after transfer to recipient females in the mouse (Sjöblom et al 2005), cow (Loureiro et al 2009; Denicol et al 2014b; embryos produced with X-sorted sperm), and human (Ziebe et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Introducing mouse GM‐CSF into embryo culture increased in vitro development of parthenotes in a protein free culture condition (Cui et al, 2004). Pig GM‐CSF had a positive effect on the in vitro development of IVF‐ and SCNT‐derived embryos (Kwak et al, 2012a, b). While positive effects of GM‐CSF on embryos has been reported, all results are restricted only to in vitro studies, thus limiting its application in vivo.…”
Section: Introductionmentioning
confidence: 99%